2020
DOI: 10.1097/aog.0000000000003696
|View full text |Cite
|
Sign up to set email alerts
|

Risk Calculator to Predict Cesarean Delivery Among Women Undergoing Induction of Labor

Abstract: OBJECTIVE: To develop and validate a predictive risk calculator for cesarean delivery among women undergoing induction of labor. METHODS: We performed a population-based cohort study of all women who had singleton live births after undergoing induction of labor from 32 0/7 to 42 6/7 weeks of gestation in the United States from 2012 to 2016. The primary objective was to build a predictive model estimating the probability of cesarean delivery after induct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
57
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(61 citation statements)
references
References 18 publications
2
57
2
Order By: Relevance
“…The AUC ROC in the derivation set and internal validation set were 0.76 and 0.74, respectively. Rossi et al [12] developed and validated a predictive risk calculator for cesarean among women undergoing induction of labor. Seven independent risk factors had been associated with an increased risk The formula used a nomogram to calculate the probability of cesarean (Figure 4).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The AUC ROC in the derivation set and internal validation set were 0.76 and 0.74, respectively. Rossi et al [12] developed and validated a predictive risk calculator for cesarean among women undergoing induction of labor. Seven independent risk factors had been associated with an increased risk The formula used a nomogram to calculate the probability of cesarean (Figure 4).…”
Section: Discussionmentioning
confidence: 99%
“…The candidate predictor variables had to be easily accessible through characteristics' data. To identify predictor variables, a systematic review of the literature was conducted [8][9][10][11][12][14][15][16]. The following variables were recorded: maternal age, height, weight, baseline body mass index (BMI), weight change during pregnancy, gestational age at delivery, premature rupture of membranes (PROM), epidural analgesia, meconium-stained amniotic uid, induction methods(oxytocin, amniotomy, disposable cervical dilator balloon, prostaglandin(Propess or Misoprostol)), neonatal sex, and neonatal birth weight.…”
Section: Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation
“…Other nomograms to predict VD have been published, and some variables that we identified as associated with VD in this study (e.g., cervical exam and BMI) have been previously reported. [17][18][19][20][21][22][23] Eggebø et al reported a model to predict VD in nulliparous patients using maternal characteristics (age, BMI, GA, prolonged labor, and cervical dilatation) and intrapartum ultrasound parameters (head-perineum distance, presence of succedaneum, and fetal position). 17 While other models were developed to predict mode of delivery in patients specifically undergoing induction of labor, [18][19][20] or included additional factors such as the presence of comorbidities (e.g., hypertension, diabetes, and abruption), 18,20 our analysis differs in that we only included nulliparous low-risk patients who did not have any other comorbidities.…”
Section: Discussionmentioning
confidence: 99%
“…Currently, several published models studied on prediction of cesarean delivery were mostly focused on the white populations [7,[11][12][13][14], whereas the data of the majority of Han ethnic backgrounds of the Chinese population are insu cient. To date, China lacks the relevant researches, and there is limited empirical evidence and clinical experience reported.…”
Section: Introductionmentioning
confidence: 99%